2008
DOI: 10.1038/sj.bjc.6604732
|View full text |Cite
|
Sign up to set email alerts
|

Second-line chemotherapy for patients with advanced gastric cancer: who may benefit?

Abstract: No established second-line chemotherapy is available for patients with advanced gastric cancer failing to respond or progressing to first-line chemotherapy. However, 20 -40% of these patients commonly receive second-line chemotherapy. We evaluated the influence of clinico-pathologic factors on the survival of 175 advanced gastric cancer patients, who received second-line chemotherapy at three oncology departments. Univariate and multivariate analyses found five factors which were independently associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 40 publications
(60 reference statements)
3
67
2
2
Order By: Relevance
“…2 Progression-free survival and overall survival curves according to the risk groups: a progression-free survival; b overall survival studies analyzed the prognostic factors for MRGC patients undergoing second-line chemotherapy. A good PS was the most important prognostic factor of second-line chemotherapy in nearly all studies [6,[23][24][25]; in addition, a higher hemoglobin level [23][24][25], longer PFS from firstline chemotherapy [6,23,25], and a lower number of metastatic sites [6,25] were reported as independent prognostic factors for OS. Shim et al [15] reported a prognostic factor analysis of third-line therapy; poor PS (ECOG PS C2), low serum albumin level (\4.0 g/dl), poor histological grade, and shorter PFS following second-line chemotherapy (\2.7 months) were factors related to poor survival outcome.…”
Section: Discussionmentioning
confidence: 98%
“…2 Progression-free survival and overall survival curves according to the risk groups: a progression-free survival; b overall survival studies analyzed the prognostic factors for MRGC patients undergoing second-line chemotherapy. A good PS was the most important prognostic factor of second-line chemotherapy in nearly all studies [6,[23][24][25]; in addition, a higher hemoglobin level [23][24][25], longer PFS from firstline chemotherapy [6,23,25], and a lower number of metastatic sites [6,25] were reported as independent prognostic factors for OS. Shim et al [15] reported a prognostic factor analysis of third-line therapy; poor PS (ECOG PS C2), low serum albumin level (\4.0 g/dl), poor histological grade, and shorter PFS following second-line chemotherapy (\2.7 months) were factors related to poor survival outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Univariate and multivariate analyses showed that elevated CEA levels [50 ng/ml were significantly associated with poor overall survival. This analysis suggests that readily available clinical factors may help to select patients with advanced gastric cancer who may benefit from second-line chemotherapy [67].…”
Section: Clinical Significance Of Serum Marker Monitoring During Chemmentioning
confidence: 98%
“…Patient selection is thus an important consideration, and several clinical factors have been associated with poor OS after secondline therapy [75]: low PS (two or more); hemoglobin ≤11.5 g/l; carcinoembryonic antigen level >50 ng/ml; the presence of three or more metastatic sites of disease; and TTP on first-line chemotherapy ≤6 months. Survival of AGC patients who received second-line chemotherapy was shown to be related to the number of adverse prognostic factors: median survival was 12.7 months (no risk factor), 7.1 months (one to two risk factors) and 3.3 months (three to five risk factors), respectively (p < 0.001).…”
Section: Reviewmentioning
confidence: 99%